The chimera of choice in UK food policy 1976–2018. Issue 4 (1st January 2021) - Burges Watson, Duika Louise; Draper, Alizon; Wills, Wendy
Abstract : Purpose: This paper presents a critical discourse analysis of "choice" as it appears in UK policy documents relating to food and public health. A dominant policy approach to improving public health has been health promotion and health education with the intention to change behaviour and encourage healthier eating. Given the emphasis on evidence-based policy making within the UK, the continued abstraction of choice without definition or explanation provoked us to conduct this analysis, which focuses on 1976 to the present. Design/methodology/approach: The technique of discourse analysis was used to analyse selected food policy documents and to trace any shifts in the discourses of choice across policy periods and their implications in terms of governance and the individualisation of responsibility. Findings: We identified five dominant repertoires of choice in UK food policy over this period: as personal responsibility, as an instrument of change, as an editing tool, as a problem and freedom of choice. Underpinning these is a continued reliance on the rational actor model, which is consonant with neoliberal governance and its constructions of populations as body of self-governing individuals. The self-regulating, self-governing individual is obliged to choose as a condition of citizenship. Research limitations/implications: This analysis highlights the need for a more sophisticated approach to understanding "choice" in the context of public health and food policy in order to improve diet outcomes in the UK and perhaps elsewhere. Originality/value: This is the first comprehensive analysis of the discourse of choice in UK food policy.